2007
DOI: 10.1128/ec.00329-06
|View full text |Cite|
|
Sign up to set email alerts
|

Role of SP65 in Assembly of the Dictyostelium discoideum Spore Coat

Abstract: Like the cyst walls of other protists, the spore coat of Dictyostelium discoideum is formed de novo to protect the enclosed dormant cell from stress. Spore coat assembly is initiated by exocytosis of protein and polysaccharide precursors at the cell surface, followed by the infusion of nascent cellulose fibrils, resulting in an asymmetrical trilaminar sandwich with cellulose filling the middle layer. A molecular complex consisting of cellulose and two proteins, SP85 and SP65, is associated with the inner and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This regulated secretion is a prerequisite for both the synthesis and the organization of cellulose in the spore coat (Srinivasan et al, 2000b;Metcalf et al, 2003). After the spore coat proteins are secreted to the extracellular side, the enzyme responsible for cellulose synthesis, cellulose synthase, is positioned in the plasma membrane and synthesizes cellulose directly into the outer layer of the spore coat (Metcalf et al, 2007;West, 2003;Metcalf et al, 2003;Srinivasan et al, 2000b).…”
Section: Roles For Hip1r In Dictyostelium Spore Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…This regulated secretion is a prerequisite for both the synthesis and the organization of cellulose in the spore coat (Srinivasan et al, 2000b;Metcalf et al, 2003). After the spore coat proteins are secreted to the extracellular side, the enzyme responsible for cellulose synthesis, cellulose synthase, is positioned in the plasma membrane and synthesizes cellulose directly into the outer layer of the spore coat (Metcalf et al, 2007;West, 2003;Metcalf et al, 2003;Srinivasan et al, 2000b).…”
Section: Roles For Hip1r In Dictyostelium Spore Formationmentioning
confidence: 99%
“…Hip1r mutant spores stain with SP70, a glycoprotein housed within the pre-spore vesicle, so Hip1r is not required for the overall secretion of PSV contents. The spore coat contains a minimum of ten different glycoproteins that are secreted through at least two different pathways (Metcalf et al, 2007;West, 2003). As a scaffolding protein with binding sites for actin, the plasma membrane and a coiledcoil domain, it is conceivable that Hip1r could be required for the proper positioning of any of the many factors involved in the organization of the spore coat.…”
Section: Roles For Hip1r In Dictyostelium Spore Formationmentioning
confidence: 99%
“…A function for these two genes in GPS biosynthesis is documented here, and this has in turn revealed that the GPS plays an important role in cellulose deposition, protein incorporation, and the resistance of spores to stress. The effect on spore stress resistance is profound: while less severe than disruption of the dcsA cellulose synthase gene itself (47), it is more severe than coat structural protein mutants examined up to now (23,30,37).…”
mentioning
confidence: 99%
“…This physicochemical barrier protects the enclosed amoeba from external stress and probably actively regulates terminal sporulation and spore germination. The spore coat is formed de novo from four known sources: (i) an early-formed pool of proteins and (ii) a galactose-rich polysaccharide (GPS) stored together in prespore vesicles (PSVs) of the slug, (iii) a late-formed pool of protein(s), including SP65 (23), and (iv) cellulose formed de novo at the cell surface. These components are separately deposited at the cell surface, where they organize into an asymmetrical trilaminar "sandwich" with proteins on either side enclosing the polysaccharides in the interior (see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation